2013
DOI: 10.1161/atvbaha.112.300407
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Inhibits Smooth Muscle Cell Proliferation and Obstructive Arteriopathy Attributable to Elastin Deficiency

Abstract: Objective-Patients with elastin deficiency attributable to gene mutation (supravalvular aortic stenosis) or chromosomal microdeletion (Williams syndrome) are characterized by obstructive arteriopathy resulting from excessive smooth muscle cell (SMC) proliferation, mural expansion, and inadequate vessel size. We investigated whether rapamycin, an inhibitor of the cell growth regulator mammalian target of rapamycin (mTOR) and effective against other SMC proliferative disorders, is of therapeutic benefit in exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 34 publications
3
40
0
Order By: Relevance
“…Consistent with previous reports, 14,32 our results showed that rapamycin significantly inhibited cell growth and promoted cell apoptosis of vascular smooth muscle cells, which was further augmented by curcumin (Figs. 7A, B).…”
Section: Curcumin Treatment Augments the Rapamycin-induced Cell Apoptsupporting
confidence: 93%
“…Consistent with previous reports, 14,32 our results showed that rapamycin significantly inhibited cell growth and promoted cell apoptosis of vascular smooth muscle cells, which was further augmented by curcumin (Figs. 7A, B).…”
Section: Curcumin Treatment Augments the Rapamycin-induced Cell Apoptsupporting
confidence: 93%
“…The role of SMC proliferation was further investigated using a pharmacological inhibitor of mTOR signaling. Rapamycin administered at 2 mg/kg/d, a validated therapeutic dose in other models of arterial disease characterized by SMC hyperplasia (34,35), resulted in whole-blood trough levels of 27.3 ± 5.0 ng/ml (n = 6). This treatment strategy inhibited mTOR and ERK1/2 signaling of KO aorta in vivo ( Figure 5G).…”
Section: Figurementioning
confidence: 99%
“…For example, diabetes increases VSMC PKC activity, nuclear factor-B (NF-B) production, and generation of oxygen-derived free radicals, all of which heighten VSMC migration and the formation of atherosclerotic lesions (16). These pathophysiological changes in VSMCs are associated with activation of mTOR, p70S6K, ribosomal protein S6, and 4E-binding protein 1 to promote protein translation and cell growth (42). Thus, inhibitors of mTOR, such as rapamycin have potent antiproliferative effects capable of hindering neointimal formation and intimal hyperplasia, and may be used as drug-eluting stents in coronary artery disease to prevent restenosis.…”
Section: Pi3k/aktmentioning
confidence: 99%